Entre a paráfrase e a polissemia : o discurso da educação feminina no Jornal das Senhoras (1852-1855) - Silva, Aguimario Pimentel (2016)
The work consists of a discursive approach of the journal O Jornal das Senhoras, which circulated in the city of Rio de Janeiro, between the years 1852 and 1855, the first founded in the city by a woman, the Argentine Joanna Paula Manso de Noronha. The journal, weekly, had the declared intention to contribute to the moral emancipation of women and their education / illustration. Our objective is to identify and analyze the discourse conveyed by the newspaper, highlighting clues of rupture and continuity of meanings in relation to the issue of female education. Such analytical work, qualitative nature, was carried from the theoretical and methodological framework of French Discourse Analysis (DA), with some contributions from the Michel Foucault and Mikhail Bakhtin’s theories about the discourse, given their relevance to the achievement of objective of the research. So, first we undertook a glance on the theoretical constructs of DA that are fundamental to the work. We highlight the senses constitution processes by exploiting the central concepts of paraphrase and polysemy. In addition, we conducted an investigation into the situation of women in nineteenth-century Brazil, giving emphasis to the processes related to the question of their education: in this stage, the intention was to get an accurate understanding of the discursive formation in which it gave the formulation / movement of O Jornal das Senhoras’ discourses. We evidenced also the four main representations that were linked to the figure of the woman, in the period: daughter, wife, mother and homemaker. From the above context, we undertake an investigation around the O Jornal das Senhoras, trying to characterize it as a periodic and placing it within the Brazilian women's press of the nineteenth century. Among the 209 editions of the journal, it was located only 20 texts that approach the female education, with regard to its relationship with the four above representations. From these texts, discursive segments were selected for analysis. The results achieved in research are discussed from an approach with considerations about gender concept (which runs through all the work), in order to understand the underlying discursive process to Jornal das Senhoras’ texts. In conclusion, we indicate that although the newspaper texts declare contribute to the change of directions around the female education, resume, significantly, institutional discourses (especially the religious discourse) that in the period, ratified the idea of male superiority over the female element. Despite the tension between old and new senses, the discourse present in the Jornal das Senhoras tend to a much paraphrastic configuration, of recovery and reformulation of existing senses, than polysemic. Are discourses that tend to the same, for reproduction and maintenance of existing social conditions and relations, which breaks the supposed progressive character often attributed to the journal.